2020
DOI: 10.1016/j.jaci.2020.01.040
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I and TLR4 responses and adverse outcomes in pediatric influenza-related critical illness

Abstract: Background: Decreased TNF-a production in whole blood after ex vivo LPS stimulation indicates suppression of the Toll-like receptor (TLR)4 pathway. This is associated with increased mortality in pediatric influenza critical illness. Whether antiviral immune signaling pathways are also suppressed in these patients is unclear. Objectives: We sought to evaluate suppression of the TLR4 and the antiviral retinoic acid-inducible gene-I (RIG-I) pathways with clinical outcomes in children with severe influenza infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…Clinically, the levels of pro-inflammatory cytokines, such as IL-6 and TNF-α, are independent and significant predictors of disease severity and death in the serum of patients with COVID-19 (Del Valle Diane Marie et al, 2020 ). In addition, these cytokines were also elevated in patients with influenza pneumonia ( Novak et al, 2020 ). By regulating cytokines, it is an effective means to treat infections.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the levels of pro-inflammatory cytokines, such as IL-6 and TNF-α, are independent and significant predictors of disease severity and death in the serum of patients with COVID-19 (Del Valle Diane Marie et al, 2020 ). In addition, these cytokines were also elevated in patients with influenza pneumonia ( Novak et al, 2020 ). By regulating cytokines, it is an effective means to treat infections.…”
Section: Discussionmentioning
confidence: 99%
“…For influenza A, several genetic variations can be identified that cause inborn errors of immunity. These affect viral replication and the inflammatory response in different parts of the immune system (32,33). Genetic variations can influence the manifestation of many infections at different levels, such as viral load, organ involvement, chronicity, malignant transformation, and severity of the acute disease (34).…”
Section: Discussionmentioning
confidence: 99%
“…Children with immunoparalysis demonstrate marked reduction in this TNFα production capacity or "TNFα response". In the most commonly used assay, a TNFα response < 200 pg/mL after stimulation of whole blood with 500 pg/mL of LPS for four hours has been repeatedly associated with mortality, increased nosocomial infection risk, and prolonged organ dysfunction in septic children [10,[12][13][14][15]. In children with critical influenza infection, the addition of provocative testing of the antiviral retinoic acid-inducible gene-I (RIG-I) pathway may have added prognostic value compared to TLR4 pathway stimulation alone [15].…”
Section: Immunoparalysismentioning
confidence: 99%